2021
DOI: 10.1093/nutrit/nuab023
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of regulatory governance factors that shape food and nutrition policies

Abstract: Food composition, marketing restrictions, nutrition labeling, and taxation policies are recommended for preventing diet-related noncommunicable diseases. In view of the increasing but variable adoption of food policies globally, this narrative review examines the actors, regulatory frameworks, and institutional contexts that shape the development, design, and implementation of these policies. We found a diverse range of actors using various strategies, including advocacy, framing, and evidence generation to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Labelling, marketing, taxation and reformulation policies have gained significant policy attention at the global and national levels, hence we thought prudent and practical to focus on these. In 2019, we conducted a narrative review of international peer-reviewed and grey literature on regulatory governance of implemented food policies (n 73) and on policy outcomes (n 224) (13) . A year after the initial review, we conducted an additional literature search to identify any studies published between August 2019 and August 2020 followed by an additional grey literature search to fill gaps in policy cases that had insufficient information on one or more regulatory governance conditions.…”
Section: Policy Casesmentioning
confidence: 99%
See 4 more Smart Citations
“…Labelling, marketing, taxation and reformulation policies have gained significant policy attention at the global and national levels, hence we thought prudent and practical to focus on these. In 2019, we conducted a narrative review of international peer-reviewed and grey literature on regulatory governance of implemented food policies (n 73) and on policy outcomes (n 224) (13) . A year after the initial review, we conducted an additional literature search to identify any studies published between August 2019 and August 2020 followed by an additional grey literature search to fill gaps in policy cases that had insufficient information on one or more regulatory governance conditions.…”
Section: Policy Casesmentioning
confidence: 99%
“…The literature review identified the roles of actors, ideas, political contexts and evidence that shaped agenda setting, design and implementation of the policy cases included in this study (13) . In this analysis, we included policies that were already adopted thus our interest was less on the contextual factors that led to policy adoption and more on the factors that shaped how the policies were eventually designed.…”
Section: High Industry Involvementmentioning
confidence: 99%
See 3 more Smart Citations